New Trends and Developments in Metrology - Cocco, Luigi (IntechOpen, 2016)
Investigating the incessant technology growth and the even higher complexity of engineering systems, one of the crucial requirements to confidently steer both scientific and industrial challenges is to identify an appropriate measurement approach. A general process can be considered effective and under control if the following elements are consciously and cyclically managed: numeric target, adequate tools, output analysis, and corrective actions. The role of metrology is to rigorously harmonize this virtuous circle, providing guidance in terms of instruments, standards, and techniques to improve the robustness and the accuracy of the results. This book is designed to offer an interdisciplinary experience into the science of measurement, not only covering high-level measurement strategies but also supplying analytical details and experimental setups.